Gadd45g, A Novel Antidepressant Target, Mediates Metformin-Induced Neuronal Differentiation of Neural Stem Cells Via DNA Demethylation. Issue 1 (19th January 2022) - Zhang, Le; Li, Qingfeng; Wang, Huan; Wu, Yuanfei; Ye, Xiujuan; Gong, Zhuo; Li, Qingqing; Xuan, Aiguo
Abstract: Increased neurogenesis elicits antidepressive-like effects. The antidiabetic drug metformin (Met) reportedly promotes hippocampal neurogenesis, which ameliorates spatial memory deficits and depression-like behaviors. However, the precise molecular mechanisms underpinning Met-induced neuronal differentiation of neural stem cells (NSCs) remain unclear. We showed that Met enhanced neuronal differentiation of NSCs via Gadd45g but not Gadd45a and Gadd45b. We further found that Gadd45g increased demethylation of neurogenic differentiation 1 promoter by regulating the activity of passive and active DNA demethylation enzymes through an adenylate-activated protein kinase -independent mechanism in Met-treated NSCs. Importantly, genetic deficiency of Gadd45g decreased hippocampal neurogenesis, which could contribute to spatial memory decline, and depression-like behaviors in the adult mice, whereas forced expression of Gadd45g alleviated the depressive-like behaviors. Our findings provide a model that Gadd45g-mediated DNA demethylation contributes to Met-induced neuronal genesis and its antidepressant-like effects and propose the concept that targeting Gadd45g regulation of neurogenesis might serve as a novel antidepressant strategy. Graphical Abstract: